Porous SiO2 Nanospheres Modified with ZrO2 and Their Use in One- Pot Catalytic Processes to Obtain Value-Added Chemicals from Furfural - Maderuelo-Solera, Rocío; Richter, Stefan; Jiménez-Gómez, Carmen Pilar; García-Sancho, Cristina; García-Mateos, Francisco José; Rosas-Martínez, Juana María; Moreno-Tost, Ramón; Cecilia-Buenestado, Juan Antonio; Maireles-Torres, Pedro Jesús (American Chemical Society, 2021)
Porous SiO2 nanospheres have been modified with different proportion of ZrO2 to obtain catalysts with Si/Zr molar ratio between 2.5 and 30. These materials were characterized by X-ray diffraction, transmission electron microscopy, scanning electron microscopy, N2 adsorption-desorption at -196 ºC, X-ray photoelectron spectroscopy and pyridine and 2-6-dimethylpyridine thermoprogrammed desorption. The characterization of these catalysts reveals that the incorporation of a high proportion of Zr favors the formation of Lewis acid sites, which are implied in catalytic transfer hydrogenation processes, whereas the low Brönsted acidity promote dehydration reaction, in such a way that it is possible to obtain a wide range of products from FUR through consecutive reactions, such as furfuryl alcohol, i-propyl furfuryl ether, i-propyl levulinate and γ-valerolactone in a range of temperature of 110-170 ºC between 1-6 h of reaction.
Keywords: Nanopartículas; Alcoholes; Catalizadores; Reacciones químicas; lignocellulose; furfural; porous silica; biorefinery; biomass valorization